Physiological Responses of Wheelchair Basketball Athletes to a Combined Aerobic and Anaerobic Training Program - Francesca Latino; Rosabel Martinez-Roig; Hendra Setyawan; Nugroho Susanto; Khoiril Anam; Emma Saraiello; Francesco Tafuri (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Among the multifarious adapted sports, wheelchair basketball stands out as a highly recommended group activity among individuals with paraplegia, including those with Spinal Cord Injury (SCI). Athletes facing this particular impairment exhibit distinct alterations in their metabolic, cardiorespiratory, neuromuscular, and thermoregulatory systems, ultimately leading to a diminished physiological respiratory capacity in comparison to able-bodied individuals or those with other forms of impairments. The primary objective of the present research endeavor is therefore to explore the impact of a comprehensive exercise regime, encompassing both aerobic and anaerobic components, upon the enhancement of the aerobic capacity of wheelchair basketball athletes. A total of 32 wheelchair basketball players, ranging in age from 34 to 42, were enlisted in the study, with half allocated to an experimental group engaging in combined aerobic and anaerobic training [EG, n = 16], while the remaining participants were assigned to a control group undertaking solely aerobic exercise training [CG, n = 16]. The 12-minute wheelchair propulsion distance was utilized to evaluate the V̇O2peak in individuals with paraplegia, both before and after the intervention. The findings revealed a significant Time x Group interaction for the 12-minute wheelchair propulsion distance variable, highlighting a notable enhancement in the treatment group (p < 0.001). In contrast, no substantial changes were detected in the control group. Thus, the outcomes suggest that the integration of aerobic and anaerobic exercise yields a highly positive impact on the aerobic performance of wheelchair basketball players.